Process consultation : building the helping relationship - Schein, Edgar H. (Addison-Wesley Pub. ReadingUS, 1999)
Defines process consultation, and explains how a healthy, helping consultant-client relationship can be achieved. Examines topics such as the psychodynamics of the helping relationship; the concept of the client; communication and deliberate feedback; group problem-solving and decision-making; and, dialogue v. sensitivity training. Presents 10 principles as the essence of process consultation.